Dimensões do conhecimento profissional na perspectiva de estudantes de educação física - Fonseca, Rubiane Giovani (2010)
Modern society is characterized by the increased value of the intellectual repertoire and the capacity for renewal that the professional should have the face of situations found in the context of intervention. Consequently, training must provide information to justify the development of knowledge that make up the work and also must consider the expectations of social demands. Therefore, we must recognize how the skills are organized and how they relate to provide meaningful answers to the field of professional intervention. In that sense, this study aims to examine how the dimensions of professional knowledge reveal themselves in the process of formation of academic bachelor's degree in physical education in order to identify the implications for academic identity and professional. We use a qualitative approach through the use of focus groups, aiming to capture the interactions between knowledge, subject and environment, as the eyes of the participants in the study. In addition to the group interviews, individual interviews conducted to confirm and strengthen concepts and themes arising in the focus groups. Study participants were 25 students from first to fourth year of Physical Education, Universidade Estadual de Maringá - UEM. The data collected were transcribed and analyzed material originated through reading, transcribing and decoding of information into categories that were grouped according to the context and the meanings attributed to objects under discussion. e obtained three main themes: "Characteristics of physical education course", which is related to impressions and qualities attributed to the training course, experienced by students. In this category, it was possible to map the division between undergraduate and graduate-heavy choices and assignments related to content and experiences throughout the training, influencing the analysis of the students about the job market and their employability. The second theme, "Characteristics of physical education professionals", students match the look on the profile of physical education teachers and the underlying elements that influence the representation of the ideal professional. We mapped the elements of value, contextual and social determinants that are in the construction of the professional ideal and guide students' choices related to the content of teaching during training. The third theme identified was "Ways to access knowledge" which refers to strategies used by students to keep up and guide their actions. We conclude that the students seem to isn't realize the academic and scientific content acquired during the course, in experiences they live outside the university. Hence the search for update with colleagues, other professionals and courses that allow to acquire technical knowledge that can be applied immediately. Moreover, we conclude that the perceptions of students about what society expects of the professional guide how they build their professional identity.